Pakistan’s Mineral Investment Forum 2025; Tapping Balochistan’s Minerals and Advancing National Economy and Foreign Policy Choices - Khan, Rahat Naseem Ahmed; Khan, Asmat Ullah (ACADEMIA International Journal for Social Sciences, 2025)
In a contemporary global economy, natural resources, especially minerals, are being used as critical instruments of economic diplomacy and statecraft.1 Countries use the notion of minerals to enhance trade relations, establish strategic alliances, and project power in international political systems.2 Pakistan is a mineral-rich country in terms of its geological sector.3 The province of Balochistan, Pakistan, has the potential for a vast untapped reserve of gold, copper, coal, chromite, and rare earth elements.4 While significant mineral resources exist, the province of Balochistan is left economically underdeveloped and Geo-politically sensitive because of various factors, including internal governance issues combined with external systemic challenges. Pakistan Mineral Investment Forum 2025 is a state-led initiative that is strategically positioned as a transformational opportunity to mobilize foreign direct investments into Pakistan, promote public-private partnerships, and establish a financially and structurally organic mineral sector in an integrated global economy.